SYNTHESIS OF METAL CARBOXYLATES FROM ALMOND SEED OIL (TERMINALIA CATAPPA (FUDMA JOURNAL OF SCIENCES, 2022)
TThe less exploited seed oil of almond was investigated for its potential utilization as a raw material for the synthesis of metal carboxylates. The oil was extracted from the almond seeds and a yield of 42% was obtained. The oil was characterized and used to synthesize the carboxylates of barium, calcium, cobalt, copper, iron, magnesium, nickel and zinc. The functional groups of fatty acid carboxylates produced were confirmed by FTIR. The characteristic colours of the carboxylates were white (barium, calcium, magnesium and zinc carboxylates), ash (Cobalt carboxylate), mint green (copper carboxylate), brown (iron carboxylate), and lemon green (nickel carboxylate). The pH of the solutions of the metal carboxylates varies from 6.6 to 10 with no free alkaline. The foam stability test revealed a length of 1.3 cm for barium carboxylate and 0.3 cm for magnesium carboxylate while other carboxylates did not foam.
Keywords: Carboxylates; almond; extraction; metathesis; infrared.